Effects of anxiety, stress and perceived social support on depression and loneliness among older people during the covid-19 pandemic: a cross-sectional path analysis - Farhang, Maryam; Álvarez Aguado, Izaskun.; Celis Correa, Javier.; Toffoletto, María Cecilia; Rosello Peñaloza, Miguel Andrés. (SAGE Publications, 2024)
During the COVID-19 pandemic, older people were exposed to high levels of anxiety and stress leading to loneliness and depressive disorders. The purpose of the present study was to investigate the effects of anxiety, positive coping, perceived social support, and perceived stress on depression and loneliness among older people during the COVID-19 pandemic. This was a cross-sectional online/telephone survey. A non-probability convenience sampling method was used. Participants were 112 people aged 60 years and above, without cognitive impairment, who experienced confinement (from March 2020 onward) and had access to the internet or telephone. A path analysis model showed a direct significant effect of anxiety on both, depression (β =.68, P <.001) and perceived stress (β =.65, P <.001), as well as an indirect effect of anxiety on loneliness via perceived stress (β =.65) * (β =.40); and social support (β = −.21) * (β = −.20). The model showed adequate fit χ2(df = 4) =5.972, P =.201; RMSEA = 0.066 (0.000, 0.169), CFI = 0.992; TLI = 0.970. Anxiety had a significant effect on depressive symptoms as well as on loneliness via perceived social support and perceived stress. According to our findings, in order to reduce depressive symptoms and perceived loneliness, it is essential to develop timely interventions that decrease levels of anxiety and stress and increase levels of perceived social support in older people, particularly when there are any restrictions, physical or contextual, that prevent face-to-face contact. This can be achieved by implementing preventive community-based programs, enhancing accessibility to mental health services, and collaborating with local support groups, among others.
Keywords: Social support; Ansiedad; Depresión; Soledad; Ancianos; Estrés